Transient and steady state CO oxidation kinetics on nanolithographically prepared supported Pd model catalysts: Experiments and simulations - Libuda, Jörg; et al. (Journal of Chemical Physics, 2005)
Applying molecular-beam methods to a nanolithographically prepared planar Pd/SiO2 model catalyst, we have performed a detailed study of the kinetics of CO oxidation. The model catalyst was prepared by electron-beam lithography, allowing individual control of particle size and position. The sample was structurally characterized by atomic force microscopy and scanning electron microscopy before and after reaction. In the kinetic experiments, the O-rich and CO-rich regimes were investigated systematically with respect to their transient and steady-state behaviors, both under bistable and monostable reaction conditions. Separate molecular beams were used in order to supply the reactants, allowing individual control over the reactant fluxes. The desorbing CO2 was detected by both angle-resolved and angle-integrated mass spectrometries. The experimental results were analyzed using different types of microkinetic models, including a detailed reaction-diffusion model, which takes into account the structural parameters of the catalyst as well as scattering of the reactants from the support. The model quantitatively reproduces the results as a function of the reactant fluxes and the surface temperature. Various kinetic effects observed are discussed in detail on the basis of the model. Specifically, it is shown that under conditions of limited oxygen mobility, the switching behavior between the kinetic regimes is largely driven by the surface mobility of CO. (C) 2005 American Institute of Physics.